Pollen aquaporins: What are they there for? - Pérez, Juliana Andrea (2016)
In order to provide more insight into the function of aquaporins during pollination, we characterized NIP4;1 and NIP4;2, 2 pollen-specific aquaporins of Arabidopsis thaliana. NIP4;1 and NIP4;2 displayed high amino acid identity. RT-PCR and GUS promoter analysis showed that they have different expression patterns. NIP4;1 is expressed at low levels in mature pollen, while NIP4;2 is highly expressed only during pollen tube growth. Single T-DNA nip4;1 and nip4;2 mutants and double amiRNA nip4;1 nip4;2 knockdowns showed reduced male fertility due to deficient pollen germination and pollen tube length. Functional assays in oocytes showed that NIP4;1 and NIP4;2 transport water and nonionic solutes. Here, the participation of the different pollen aquaporins in pollen hydration and pollen tube growth is discussed.